Peran Penyuluh Terhadap Partisipasi Petani Pada Program Pendampingan Kelompok Di Kecamatan Blora - Wahyudi, Achmad Fahrul; Sumekar, Wulan; Prasetyo, Agus Subhan (Jurnal Ekonomi Pertanian dan Agribisnis, 2024)
This research aims to obtain information on the role of agricultural extension workers and farmers’ participation in group assistance programs and analyze the effect of agricultural extension workers on farmers’ participation in the group assistance program. The method used in this research is a survey method through purposive sampling by considering members of farmer groups still active in mentoring programs. Primary data collection used interviews and observation, while secondary data used documentation. This research used descriptive analysis and Multiple Linear Regression analysis with an   SPSS application. The results showed that 59 farmers (49%) assessed the role of agricultural extension workers in the moderate category, 37 farmers (31%) low category, and 24 farmers (20%) high category. The level of farmers’ participation in the group assistance program is in the moderate category. The role of the agricultural extension workers as an educator, facilitators, motivators, and evaluators partially had a significant effect on the involvement of farmers in group assistance programs in the Blora District. In contrast, as a communicator hadn’t a significant effect. The role of agricultural extension workers as an educator, facilitators, communicators, motivators, and evaluators significantly affected farmers’ participation in group assistance programs in Blora District.